Cadeia voluntária: uma solução para o pequeno varejista: o caso de Brasília - Montanher, Fernando (1979)
This essay, submitted to the Marketing Department of the Escola de Administração de Empresas de São Paulo - Fundação Getúlio Vargas, in partial fulfilment of the requeriments of the Master's Degree-in Busínes. Asdministration; presents the situation of small scale grocers - their organizational structure, objectives and operational methods. This study has been divided into seven chapters. First, the author examines the dynamic aspects of the distribution flow where changes occur due to alteration of management objectives and strategies in the channel or interested agencies, as a mirror of environmental needs. From this standpoint , the significant éhanges which have ocurred in Brazil and the necessity of providing functional specialization for the people who make up the actual distribution system are viewed. It then covers the evolution and present day struc ture of the institution chich integrates the retail and whole sale business, the voluntary chain, as a consistent answer within its native land as well as other countries, in the search for efficiency and affectiveness in the distribution of products. Its offers explanation, at the same time, of the operational, political and organizational models. It presents the analysis of the small scalers in the towns surrounding Brasília, which reveals their lack of ony organization, qualified Iabour force or sufficient funds, and it pIaces stress on the voluntary chain as an aIternative solution to this faulty situation by means of adequate technological assistance. Adopting the system, it foresees the gradual eIimination of the dyadic supply Iines of the population which always favour the higher income bracket. FinaIly, the author estabiIishes normative, operitional and programmatic features consequent upon his anaIysis of the situation.